Surface modification of porous polymeric materials using low-temperature plasmas - Steen, Michelle L., author; Fisher, Ellen R., advisor (Colorado State University. Libraries, 2001)
This dissertation describes plasma surface modification of porous polymeric materials for permanent hydrophilicity. Our modification strategy entailed treating commercial polymeric membranes downstream from an inductively-coupled radiofrequency plasma source. The results presented in this dissertation demonstrate that H2O plasma treatment achieves hydrophilic modification of polysulfone (PSf), polyethersulfone (PES), and polyethylene (PE) membranes. The observed increase in hydrophilicity observed for PSf, PES, and PE membranes is a direct result of covalently-bound O-H, C-O, and C-O, (e.g. C=O, O=C-O) groups introduced by plasma treatment, furthermore, our hydrophilic membrane modification is permanent as plasma-treated membranes remain wettable for more than one year after treatment. The depth of penetration of the hydrophilic membrane modification achieved was explicitly tested. Specifically, environmental SEM images of the membrane cross sections wetting in situ show whether hydrophilic surfaces were created throughout the porous structure. Overall, the extent and permanence of hydrophilic modification was correlated to the interactions between the membrane and reactive plasma species and the degree of penetration of plasma species through the membrane. This dissertation examined the underlying chemistry of the H2O plasma surface modification system using three gas-phase analytical techniques. These analyses provided a comprehensive profile of plasma species and extensive data on the molecular-level chemistry from the gas phase, to the plasma-surface interface, to the actual surface modification. Characterization of gas-phase species, including those penetrating the membrane thickness, as well as molecules generated at the membrane surface during modification was performed using optical emission spectroscopy and mass spectrometry. Plasma-surface interactions of OH radicals were assessed with our direct, non-intrusive radical-imaging experiments based on laser-induced fluorescence (LIF). Collectively, these experiments provide information about the underlying chemistry occurring during surface modification and. ultimately, afford belter process control for plasma treatments of polymeric materials. Our LIF-based radical-imaging and mass spectral experiments were also brought to bear on a second plasma surface modification system to understand the mechanisms through which surfaces are made hydrophilic during NH2 plasma treatment. Interactions of NH and NH2 radicals with polymer and metal substrates during NH2 plasma processing were investigated using our radical-imaging experiments. Gas-phase species, including nascent plasma ions, were identified using mass spectrometry. To investigate the role of ions on the formation of NHx radicals in the gas phase and at the surface, ions were removed (>98%) from the plasma molecular beam prior to interaction with the substrate. Surface interaction results for NH and NH2 with and without ions provide the basis for a discussion of possible surface interactions for the polymer and metal substrates examined. This dissertation also employed plasma deposition to produce tailored surface coatings for microporous polymeric materials. These coatings, designed for specific uses, were integrated throughout the porous structure. Considerable control of the film chemistry was achieved through downstream and pulsed plasmas. In addition, a combination of synthetic strategies were employed to synthesize concentric-tubular Au. polymer micro- and nanostructured composites. This involved the use of template synthesis to produce the inner gold tubules and plasma deposition to create the outer tubules. These systems demonstrate the range of materials chemistry and surface properties possible for integrated composites prepared using plasma deposition as one of the synthetic steps.
Keywords: analytical chemistry; polymers; polymer chemistry